Catalyst characterization and catalytic evaluation of 3wt%Al-KIT-6 toward biomass-derived γ-valerolactone decarboxylation to butene. (15th September 2022) - Yu, Haibiao; Wang, Peng; Du, Xinwei; Feng, Xiaogeng; Cui, Junshuo; Lou, Zhenning; Shan, Weijun; Xiong, Ying
Graphical abstract: Highlights: High active 3 wt%Al-KIT-6 for GVL to butene was prepared by simple method. 94.28% butene yield can be obtained over 3 wt%Al-KIT-6 at 300 ℃. The activity of 3 wt%Al-KIT-6 was satisfactory after 9 cycle tests. Proper amount H2 O was beneficial to the reaction by inhibiting carbon deposition. Abstract: Biomass-derived γ-Valerolactone (GVL) has been identified as a promising, sustainable platform molecule. The production of butene from GVL is of great significant in the situation of the fossil fuel resource crisis. In present work, x wt%Al-KIT-6 catalyst were prepared and employed for catalyzing GVL decarboxylation to butene. It was found that the suitable Brønsted/Lewis acid ratio and large amount of weak acid sites played a major role for the decarboxylation of γ-protonated pentenoic acid (PEA), which endowed 3wt%Al-KIT-6 with excellent catalytic performance. Over the 3wt%Al-KIT-6 catalyst, the GVL conversion and butene yield can up to 99.68% and 94.28% at 300 ℃, respectively. The corresponding E a was as low as 86.97 kJ·mol −1 . Moreover, 3wt%Al-KIT-6 also exhibited an outstanding regenerable performance for cycle tests. Most importantly, the presence of an appropriate amount of H2 O was beneficial to catalyzing GVL decarboxylation to butene by inhibiting the deposition of carbon.